The In-Vitro Antitumor Effects of AST-3424 Monotherapy and Combination Therapy With Oxaliplatin or 5-Fluorouracil in Primary Liver Cancer - Zhang, Yu; Qin, Shukui; Chao, Jiaojiao; Luo, Yan; Sun, Yandi; Duan, Jianxin (Frontiers in Oncology, 2022)
Background Primary liver cancer (PLC) is a common and highly lethal malignancy in the world. Approximately 85% of PLC is hepatocellular carcinoma (HCC), and this study mainly focuses on HCC. The onset of liver cancer is insidious and often complicated with basic liver disease. Meanwhile, its clinical symptoms are atypical, and the degree of malignancy is high. What is worse is that its treatment is difficult, and the prognosis is poor. All these factors make its mortality close to its incidence. AST-3424 is a prodrug of a potent nitrogen mustard, which targets the tumor by its specific and selective mode of activation and results in the concentration of the drug in the tumor and plays a higher intensity of antitumor effect with reduced side effects. The purpose of this study was to explore the in-vitro antitumor activity and mechanism of AST-3424 monotherapy and combination therapy with oxaliplatin (OXA) or 5-fluorouracil (5-Fu). Moreover, it can provide an experimental basis for further studies. Methods Tumor growth of HCC cells was examined by using the Cell Counting Kit-8 (CCK-8), flow cytometry, and clone formation assays. Tumor migration of HCC cells was examined by using the Transwell assay. The in-vitro antitumor activity of AST-3424 monotherapy and combination therapy with OXA and 5-Fu was quantified by growth and metastasis inhibition rate. The underlying molecular mechanism was investigated by using Western blotting. Results The inhibiting effects of AST-3424 were significant in both HepG2 cells and PLC/PRF/5 cells. Moreover, HepG2 cells showed higher sensitivity to AST-3424. With increasing AST-3424 concentration, AKR1C3 protein expression level was downregulated significantly. The inhibition of AST-3424 was significantly higher than OXA, 5-Fu, Sor (sorafenib), and Apa (apatinib) in both HCC cells. AST-3424 monotherapy and combination therapy with OXA or 5-Fu all strongly inhibited the proliferation of HCC cells, blocked HCC cells in the S phase, promoted apoptosis induction, and suppressed the migration of HCC cells. Among them, the antitumor effect of AST-3424 in combination with OXA was obviously enhanced. Western blotting analysis demonstrated the regulation of P21, Bax, Caspase3, PARP, MMP-2, MMP-9, and p-Smad proteins in the presence of AST-3424 monotherapy and combination therapy with OXA or 5-Fu, indicating that its antitumor mechanisms may be associated with the regulation of the TGF-β signaling cascade. Conclusion The in-vitro studies revealed that AST-3424 in combination with both OXA and 5-Fu showed an increased antitumor effect, and the combination with OXA resulted in a synergistic effect. Together with the in-vitro results, additional in-vitro and in-vivo studies are warranted to further certify its antitumor effects and explore more potential antitumor mechanisms.